Determinan Hasil Belajar Praktikum Akuntansi Perusahaan Jasa, Dagang, dan Manufaktur Siswa SMK Negeri 1 Ngawi Melalui Google Classroom - Lisa Apriyana; Elva Nuraina; Nur Wahyuning Sulistyowati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The following research aims to partially and simultaneously test the level of participation, discipline, family environment, learning motivation, and learning facilities on the learning outcomes of the Accounting Practicum for Service, Trade, and Manufacturing Companies of SMK Negeri 1 Ngawi students. This type of research uses quantitative methods with data collection techniques using questionnaires and documentation. This research was carried out on class XI students of SMK Negeri 1 Ngawi with a population of 139 respondents as well as being used as samples. The results prove that partially only the level of participation, family environment, and learning motivation simultaneouslyaffect learning outcomes, while partially all variables affect learning outcomes.